The Economics of Belonging : A Radical Plan to Win Back the Left Behind and Achieve Prosperity for All - Sandbu, Martin E. (Book collections on Project MUSE., 2020)
"This is a proposal for a short book (of around 50,000 words) that speaks directly to the state we are in. The populist insurgency on both sides of the Atlantic and in Europe has deep roots in decades of mismanagement of economic and cultural change and as a result there are large groups of people who feel they no longer belong to the societies they live in, the disinfranchised, the left behind. The appeal of the anti-liberal populists who have emerged is that they convince those who feel left behind that national leaders are no longer working in their interests hence the rhetoric of 'putting America first' and 'making America great again' or the Brexiteers claining that they are 'taking back control.' In undemocractic regimes elsewhere populists play on people's feelings of insecurity in an unpredictable and fast changing world, promising security and order in exchange for democratic freedom. Liberal openness has been put on the defensive so it is up to us, electorates, politicians and policy makers, to show how an open and liberal economic system can once again belong to everyone. In the second part of the book Martin Sandbu outlines four key areas of economic policy that he believes will address not just the symptoms but the underlying causes of the current inequality which has led to so many people, especially the young and the most vulnerable being left behind. These include productivity, regional development, improved access to business finance for SMEs, and increaed representation for workers. He makes a number of other recommendaitons regarding housing, education for all, universal basic income and taxation. He concludes by saying that while these proposals add up to a radical package in total they are necessary reforms to ensure a sense of belonging and without them we could be opening the door to a radicalism which is both illiberal and undemocratic"--